Corrigendum to "Modeling of asphalt roof shingle-sealant structures for prediction of local delamination under high wind loads" [Eng. Struct. 96 (2015) 100–110]. (1st September 2016) - Croom, Brendan P.; Sutton, Michael A.; Zhao, Xing; Matta, Fabio; Ghorbani, Rahim; Aleshin, Artem
Abstract: The authors regret that they have identified a miscalculation in the original article that required the authors to provide corrective additions that are listed below. Specifically the authors determined that the shingle uplift pressure, p 1 = 12.5 Pa, used in the original article (Croom et al., 2015) is associated with a 40 km/h (25 mph) wind velocity instead of 145 km/h (90 mph). A miscalculation of pressure values due to inaccurate unit conversion was the source of the misstatement. The corrected interior uplift pressure is p 1 = 183 Pa for a 145 km/h (90 mph) wind velocity and p 1 = 507 Pa for a 241 km/h (150 mph) wind velocity. Additional simulation results have been performed for the corrected pressures and the results are reported in this Corrigendum.